(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This work recommends the use of an algorithm to solve a number of engineering problems related to transient conduction during the various processes associated with heat transfer through a single or multilayer wall. A detailed study of the steady-state thermal conductivity in a two-dimensional rectangular domain is carried out. Using numerical methods specific to the solution of the heat conduction equations, a model has been used which gives accurate representations of the heat distribution in the given geometry. The focus of this study is aimed at deepening the practical implications of the used numerical methodology. The results obtained from analysis highlight the potential for optimizing processes related to heat conduction in various engineering fields. The proposed numerical approach reveals opportunities for precise modelling and improvement of the thermal characteristics of various systems especially applicable in electronics, industrial systems and the implementation of modern thermal insulation materials.